Glomus tumor of uncertain malignant potential - Baral, R; Limbu, H (Journal of Pathology of Nepal, 2011)
Glomus tumors closely resemble the normal glomus body and have a predilection for skin and subcutaneous tissue. Clinically, Glomus tumors are present on the nail bed and are of less than 1 cm. We report a case of a male who presented with a 3 month history of swelling in the left thumb which was mildly tender. The swelling measured 6 x 6.5 cm. On microscopy the tumor showed mild atypia with increased mitotic activity. These features, by current definition, would suggest uncertain malignant potential. Keywords: Glomus tumor; Glomangioma; Merkel cell carcinoma. DOI: 10.3126/jpn.v1i1.4457 Journal of Pathology of Nepal (2011) Vol.1, 66-68